Shadow makers - Newman, Paul; Tony Garnett; Roland Joffe; Bruce Robinson (Los Angeles, Calif. Paramount pictures, 1989)
"In the remote desert of New Mexico, "The Manhattan, Project' is materializing -- the World Way II effort to build tha atomic bomb. Oscar winner Paul Newman (Hud, Nobody's Fool) stars as General Leslie Groves, the military man in charge of a massive project that will produce two weapons: "Fat Man" and "Little Boy." Dwight Schultz ((The Temp, Star Trek: First Contact) is J. Robert Oppenheimer, the brilliant scientist attempting to bring the startling mission to fruition. And Bonnie Bedelia, John Cusack, Laura Dern and Natasha Richardson co-star in this "stunning ... profoundly moving" film (Michael Medved, Sneak Previews) that re-creates on of history's most compelling chapters ... One that resulted in the mushroom-shaped specter that changed the world forever."--Cover.
Distributed in the Philippines by Magnavision home video.
Novelization from penguin books.
Music by Ennio Morricone ; Director of Photography Vilmos Zsigmond, A.S.C. ; Executive producer John Calley ; Screenplay by Bruce Robinson and Roland Joffe ; Story by Bruce Robinson ; Produced by Tony Garnett ; Directed by Roland Joffe ; A paramount picture.
Dwight Schultz, Bonnie Bedelia, John Cusack, Laura Dern, John C. McGinley
Keywords: Nuclear weapons -- Fiction; Nuclear weapons -- united States